Interests and concerns regarding medical marijuana among chronic pain patients in Ohio: an online survey - Daniel Adams; Nana Ama Ofei-Tenkorang; Patrick Connell; Alexa Owens; Aaron Gothard; Dmitri Souza; Samer Narouze (BMC, 2021)
Abstract Background Since the legalization of medical marijuana (MMJ) in Ohio in 2018, many chronic pain (CP) patients have become interested in it as an alternative or adjunct to prescription opioids. This has not only created a need for pain management specialists to learn about this potential indication for MMJ but also for them to have more detailed knowledge of patient attitudes and willingness to comply with providers' recommendations regarding its safe use with other pain medications. For this purpose, we surveyed CP patients in a region severely affected by the opioid crisis in order to provide better education, formulate treatment plans, and develop clinical policies. Methods We designed and administered the Medical Marijuana Interest Questionnaire (MMIQ) online to patients of the Western Reserve Hospital Center for Pain Medicine (CPM) with a diagnosis of CP who were not yet using MMJ. Questions addressed demographic and clinical characteristics, willingness to consider MMJ, and compliance with treatment plans and concerns. We then carried out a statistical analysis including Pearson chi-square, Spearman's rho and Kendall's tau tests to measure associations between variables to identify factors that may influence willingness to use MMJ. Results After sending 1047 email invitations to complete the MMIQ, 242 (23.1%) completed questionnaires were returned. The average age range of all respondents was 51-60 years, 171 (70.7%) were female and 147 (60.7%) were current opioid users. The 204 (84.3%) respondents who were willing to consider using MMJ were given access to the entire questionnaire. Of these, 138 (67.6%) reported wanting to use less opioids after starting MMJ and 191 (93.6%) were amenable to following their pain specialists' recommendations about using MMJ concurrently with opioids. Their greatest concern on a 0-5 scale was affordability (2.98) and there was a statistically significant negative correlation between older age and preference for inhaled forms (p = 0.023). Conclusion The MMIQ was successful in eliciting important data regarding patients' attitudes about MMJ for opioid titration and potential compliance. Our study was limited by being administered online rather than in-person, which skewed the demographic makeup of the sample. The MMIQ can be used to study similar populations or adapted to patients already using MMJ. Similar surveys of MMJ-experienced patients could be combined with chart reviews to study the success of these products for pain control and opioid substitution.